2020
DOI: 10.1002/acr.24044
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Adalimumab in Patients With Polyarticular Course of Juvenile Idiopathic Arthritis: STRIVE Registry Seven‐Year Interim Results

Abstract: Objective To evaluate safety and effectiveness of adalimumab (ADA) in polyarticular‐course juvenile idiopathic arthritis (JIA) in the STRIVE registry. Methods STRIVE enrolled patients with polyarticular‐course JIA into 2 arms based on treatment with methotrexate (MTX) alone or ADA with/without MTX (ADA ± MTX). Adverse events (AEs) per 100 patient‐years of observation time were analyzed by registry arm. Patients who entered the registry within 4 weeks of starting MTX or ADA ± MTX, defined as new users, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This is mainly due to methodical reasons, since younger age at baseline comes along with longer observation time in the BIKER registry. However, younger children are generally more susceptible to infectious diseases, as was also found in the STRIVE registry [ 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…This is mainly due to methodical reasons, since younger age at baseline comes along with longer observation time in the BIKER registry. However, younger children are generally more susceptible to infectious diseases, as was also found in the STRIVE registry [ 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…These findings were also consistent with data from the real-world STRIVE registry in patients with active polyarticular JIA. 23 24 In the 7-year interim analysis of STRIVE, the rate of serious AEs was 7.2/100 PY and the rate of serious infections was 2.0/100 PY with 1855.5 PY of adalimumab exposure (± methotrexate). Similar results were demonstrated in the German BiKeR registry in patients with polyarticular JIA (serious AEs, 11.0/100 PY; serious infections, 5.5/100 PY).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the treatment with adalimumab is safe and efficient in patients with JIA. 2,[37][38][39][40] Apparently, adalimumab was well tolerated, efficient, and safe in young patients with pJIA aged two to four years and those older than four with <15 kg. 41 Seven-Year Interim Results from the STRIVE Registry showed that adalimumab was well tolerated and efficient in the majority of treated children with pJIA.…”
Section: Etanerceptmentioning
confidence: 93%
“…23,37,38 Combined usage of adalimumab with non-biological DMARDs (namely methotrexate) enhances the drug efficiency. [37][38][39] According to German Biologics Registry, adalimumab is highly effective in children and adolescents with inflammatory conditions. Moreover, the treatment with adalimumab is safe and efficient in patients with JIA.…”
Section: Etanerceptmentioning
confidence: 99%